2014
DOI: 10.6018/ijes/14/1/155211
|View full text |Cite
|
Sign up to set email alerts
|

Length of stay abroad: Effects of time on the speech act of requesting

Abstract: By means of a discourse completion test (DCT) and a discourse elicitation test (DET) this study investigates the awareness and production of requests and request act modifiers of 104 nonnative speakers of English from 31 nationalities during different lengths of stay in the UK. The paper first of all provides a brief overview of studies that deal with pragmatic development and periods abroad and then, describes the data collection procedure and methodology employed. Results show that the early stages of a stay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
(32 reference statements)
3
9
0
Order By: Relevance
“…It was at later stages when learners developed their productive skills, evident in the use of a wider repertoire of request act modifiers. Our findings are in line with Vilar-Beltrán (2014) in that recognition is more evident during the first semester of immersion. Drawing from this author's findings, we propose the tentative hypothesis that production of routines would develop at later stages, while recognition will develop earlier.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…It was at later stages when learners developed their productive skills, evident in the use of a wider repertoire of request act modifiers. Our findings are in line with Vilar-Beltrán (2014) in that recognition is more evident during the first semester of immersion. Drawing from this author's findings, we propose the tentative hypothesis that production of routines would develop at later stages, while recognition will develop earlier.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…In sum, in spite of the fact that much previous research has suggested that at least one semester abroad is necessary for students to make measurable progress in certain language areas and that longer stays are generally more beneficial for L2 learners (e.g., Dwyer, 2004;Ife et al, 2000;Vilar Beltrán, 2014), the present study shows that intensive summer programs that include at-home coursework coupled with a subsequent short-term SA program can effectively promote language development in all skill areas for most students, corroborating previous research (e.g., Allen & Herron, 2003;Savage & Hughes, 2014;Watson et al, 2013) on vocabulary and grammar (e.g., Freed, 1990;Grey et al, 2015;Menard-Warwick & Palmer, 2012) and on writing gains in SA (e.g., Cubillos, 2004). That said, it should also be pointed out that several students did not increase their language skills at all, and a few students had lower posttest than pretest scores.…”
Section: Knowledge Of Vocabulary and Grammarmentioning
confidence: 92%
“…However, some scholars have found that length of residence in the target country does not have a significant effect on learners' pragmatic competence (e.g., Alcón-Soler, 2015; Kondo, 1997;Rodriguez, 2001;Vilar-Beltrán, 2014). To the best of our knowledge, no study has analyzed the effect of previous experiences abroad on learners' pragmatic performance in EMI students.…”
Section: Some Studies On Classroom Pragmatics Research Have Also Revementioning
confidence: 92%
“…Finally, another dimension influencing pragmatic development is related to claims that study abroad (SA) programs, language showers, and sojourns offer learners opportunities to develop pragmatic competence. The main focus has been the effect of length of stay on pragmatic development, with studies revealing inconclusive findings (e.g, Achiba, 2003;Kondo, 1991;Matsumara, 2001;Röver, 1996;Vilar-Beltrán, 2014). Bearing all the above in mind, the present study also explores the effect of learners' previous language experiences in terms of length of stays in English-speaking countries on pragmatic performance.…”
Section: Table Of Contentsmentioning
confidence: 96%
See 1 more Smart Citation